Gambaran Penggunaan Sumber Air Minum dan Sanitasi Jamban pada Anak-anak di Pusat Pengembangan Anak ID-127 Kelurahan Ranomuut Kota Manado - Palandeng, Henry Malcom Frank; Sapulete, Margareth R.; Porajow, Zwingly Christian J.G.; Laato, Sartika S. (UNIVERSITAS SAM RATULANGI, 2013)
Abstract: Universal Precautions are prevention acts that must be done by all of the health workers to prevent the infection spreading from the patients or vice versa. The purpose of this research is to measure the overview of the implementation of universal precaution in Kolongan Community Health Center. The research method is surveillance descriptive research with Total Sampling method as the sample collecting method.There are (13.33%) of the respondents do not wash their hands appropriately with soap, (17.78%) do not wash their hands before doing medical examination to patients, (4.44%) do not wash their hands after doing medical examinations to patients, (2.22%) do not wash their hands if skin is contaminated with blood or body fluids, (6.67%) do not wear gloves anytime they may come in contact with blood or body fluids. There were (6.67%) do not always wear gloves when cleaning up blood and body fluids soiled objects and (17.78%) do not always use masks when doing medical examination to tuberculosis or other droplet diseases patients. We found out that (6.67%) and (8.89%) do not always disinfect the medical instruments before and after using and do not always clean up the medical instruments with flowing water and soap before and after using, (24.44%) do not always clean up the medical instruments that may not contaminated with pathogens, such as linen, wheel chairs, infuse pumps before and after using. Nevertheless, all of the respondents agreed that there are proper needles and sharps disposals, and all of the respondents always dispose all needles and other sharps promptly to each of their disposals, all of the respondents agreed that there are separated disposals for medical and non medical wastes, and all of the respondents always dispose the wastes properly to the separately disposals. Conclusion: in Kolongan Community Health Center, the overview of the implementation of universal precautions is good. Keywords: Universal Precautions, Infection, Kolongan Community Health Center.